Estudio de factibilidad para la creación de una comercializadora de productos agrícolas en el recinto el Paraíso la 14 del cantón Buena Fe, Año 2013. - Montesdeoca Zambrano, Lilibeth Noemi (2015)
This research was conducted at the precinct El Paraiso - Canton Buena Fe, which has 108 farmers. It consisted of a technical, organizational, economic, and financial evaluation market research, projected 5-year term in order to give the investor a support tool for the creation of a trading company for agricultural products in town. This will encourage farmers and investors to simplify processes for the sale of their agricultural products, knowing that in this place does not exist this kind of service, so it will be an advantage over competitors. For the registration of information a questionnaire was used to survey farmers in the area to determine its criteria on quality, price, quantity and what products they sell. The actual net value is positive $ 540.849,50, which is the liquid return value generated by the project. Therefore it is feasible………………